Pendidikan Anak dalam Islam - Sukatin, Sukatin; Amrizal, Amrizal; Faridah, Farah; Amaliyah, Amaliyah; Nurhidayat, Bella Rahma; Tari, Najwa Rahmanda (Multiverse: Open Multidisciplinary Journal, 2023)
Islamic children's education adopts a holistic approach encompassing spiritual, intellectual, social, and moral dimensions. Rooted in the Quran and Hadith, it aims to cultivate individuals who adhere to divine teachings, exhibit exemplary character, and actively contribute to society. Central to this process are parents, who serve as primary guides and role models for their children. Furthermore, Islam advocates for the acquisition of practical knowledge and skills relevant to daily life. Emphasizing the significance of a nurturing environment, Islamic education underscores the consistent practice of Islamic values. Through this framework, Islam perceives children's education as a means to nurture a generation characterized by integrity and accountability, capable of meaningful societal engagement and attaining fulfillment both in this life and the hereafter.